Analysis of Modern Methods Used in English Listening Comprehension - Allaberdieva Gulshoda Bakhtiyarovna (Web of Journals Publishing, 2023)
In the article, the solution to issues related to the methodology of monitoring listening comprehension, in particular, issues such as teaching listening comprehension as a type of speech activity and skill, programmatic requirements for teaching listening comprehension, and a system of exercises aimed at teaching listening comprehension studied. Also, the specific features of the English language teaching process, the program requirements for teaching oral speech, the specific features of listening comprehension as a type of speech activity, and the program requirements for listening comprehension were analytically studied.
Keywords: listening comprehension, oral speech, program requirements, educational speech situation, communication process, teaching to speak English.